The World Bank Annual Report 2004 : Volume 1 (Year in Review) - World Bank (World Bank Annual Report, 2004)
Contents of Volume 1: Message from the Chairman, The Board of Executive Directors, The World Bank Group, The Development Agenda, Regional Perspectives, Thematic Perspectives, Improving Development Effectiveness, Summary of Fiscal 2004 Activities, and About the World Bank